Sharing Economy Meets Public Transport — The New Passenger Transport Act - Petra Ritzer-Angerer (Wirtschaftsdienst)
Abstract The new Passenger Transport Act came into force on 1 August 2021. It defines new forms of mobility. The reform contains two innovations: Firstly, a new occasional transport service, bundled on-demand transport, is permitted, creating the legal basis for such mobility services. Secondly, the new law allows for demand-responsive scheduled transport as a supplement to regular local public transport. Criticism of the new law has been voiced on different grounds. It remains to be seen what effects the law will have and the need for reform it will trigger in the future.